Advancements and Prospects in Algal Biofuel Production: A Comprehensive Review - Halina Falfushynska (Phycology)
Microalgae represent a valuable renewable resource for biofuel production due to their high lipid content, rapid growth rates, and non-competition with food resources. Both freshwater species like Chlorella and marine species such as Dunaliella, Tetraselmis, and Nannochloropsis are among the most commonly utilized candidates. This review provides a comprehensive overview of current cultivation and harvesting methodologies for microalgae in the context of biofuel production, emphasizing sustainable aviation fuel and biohydrogen. It synthesizes recent findings, technological advancements, and practical implementations to enhance the productive and economic viability of microalgae-based biofuels, highlighting their potential as a sustainable renewable energy source. Among the biofuels, sustainable aviation fuel and biohydrogen stand out as significant contributors to reducing greenhouse gas emissions. Technologies such as the oil-to-jet process and Fischer–Tropsch synthesis are being optimized to convert algal lipids into high-quality fuels. Biohydrogen offers several advantages, including the potential for negative CO2 emissions and compatibility with existing hydrogen infrastructure. Despite the challenges associated with the high costs of cultivation and processing, advances in biotechnological methods and process engineering promise to overcome these barriers. This review highlights the importance of continued research and development to maximize the potential of microalgal biofuels in achieving sustainable energy goals and contributing to global efforts in mitigating climate change.